(-27)^4/3 No Clue!

Follow Math Help Forum on Facebook and Google+

(-27)^4/3 = 81 Think of it as (-27)^4; then cube root that result. So (-27)^4 = 531441; 531441^(1/3) = 81

Originally Posted by AfterShock (-27)^4/3 = 81 Think of it as (-27)^4; then cube root that result. So (-27)^4 = 531441; 531441^(1/3) = 81 Or: [(-27)^(1/3)]^4 = [-3]^4 = 81 which doesn't require a calculator. The basic rules here are that x^(ab) = [(x^a)]^b = [(x^b)]^a and x^(1/b) = the "b"th root of x. ie. x^(1/2) = sqrt(x), x^(1/3) = cube root (x), etc. -Dan